Force-velocity profiling of sprinting athletes: single-run vs. multiple-run methods - Helland, C.; Haugen, T.; Rakovic, E.; Eriksrud, O.; Seynnes, O.; Mero, A. A.; Paulsen, G. (European Journal of Applied Physiology, 2019)
Purpose: This study explored the agreement between a single-run and a multiple-run method for force-velocity (Fv) profiling of sprinting athletes; we evaluated both absolute values and changes over time caused by sprint training. Methods: Seventeen female handball players (23 ± 3 years, 177 ± 7 cm, 73 ± 6 kg) performed 30 m un-resisted and resisted sprints (50, 80 and 110 N resistance) before and after an 8-week sprint training intervention. Two approaches were used to calculate theoretical maximal velocity (v0), horizontal force (F0), power (Pmax), and the force-velocity slope (SFv): (1) the single-run method, based on inverse dynamics applied to the centre-of-mass movement, was calculated from anthropometric and sprint split time data; and (2) the multiple-run method, where peak velocity from un-resisted and resisted sprints were plotted against the horizontal resistances. Results: Trivial differences in v0 (0.7%) were observed between the two calculation methods. Corresponding differences for F0, Pmax and SFv were 16.4, 15.6 and 17.6%, respectively (most likely; very large effect size). F0 showed poor agreement between the methods (r = 0.26 and 0.16 before and after the intervention). No substantial correlation between the changes (from pre- to post-training tests) in SFV calculated with the single-run and the multiple-run methods were observed (r = 0.02). Conclusions: This study revealed poor agreement between the Fv relationships of the investigated calculation methods. In practice, both methods may have a purpose, but the single-run and the multiple-run methods appear to measure somewhat different sprint properties and cannot be used interchangeably.